The Dimension of Maqaṣid in the Tafsir of Al-Manar by Muhammad 'Abduh and Rashid Riḍa on the Verses of Polygamy - Akhmad Baihaqi; Ayu Hanifah (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
The ongoing debate on polygamy in Islam highlights the urgency of Qur’anic interpretation that goes beyond legal-formal readings and incorporates the ethical and social objectives of Islamic law. In this context, Tafsīr al-Manār by Muḥammad ʿAbduh and Rashīd Riḍā represents a significant reformist exegetical work that responds to modern human and social challenges through a rational and maqāṣid-oriented framework. This study examines in depth the dimension of maqāṣid al-sharīʿah in the interpretation of polygamy-related verses in Tafsīr al-Manār, particularly QS al-Nisāʾ [4]:3 and related passages. The primary objective of this research is to uncover the maqāṣid-based construction of polygamy developed by ʿAbduh and Riḍā and to analyze its relevance to contemporary discourses on justice and family welfare. This research employs a qualitative-descriptive approach using content analysis, supported by thematic (mawḍūʿī) interpretation and critical textual analysis of the exegetical text. Primary data are drawn from Tafsīr al-Manār, while secondary sources include classical and contemporary works on Qur’anic exegesis, maqāṣid al-sharīʿah, and Islamic family law. The findings demonstrate that polygamy is not treated as an ideal normative practice but as a socially conditioned concession that is strictly constrained by the objectives of Islamic law, particularly justice, the protection of women’s dignity, and family stability. This study underscores the contribution of Tafsīr al-Manār to the development of a contextual and human-centered maqāṣid-based paradigm of Qur’anic interpretation.